Analyzing housing market and price fluctuation among 22 regions in Tehran: An assessment between 2015 and 2018 (Architecture Image Studies, 2023)
An unusual/unprecedented housing market fluctuation was investigated in Tehran. According to the report published by the Central Bank in Iran, “Changes in Tehran housing market in May 2018” shows a significant drop in the housing market. The Economic Research and Policy Department of The Central Bank Iran https://tsd.cbi.ir/display/content. aspx published a report based on Tenement Management Information System (TMIS) (http://www.iranamlaak.ir/) data. These reports show an uneven housing market growth in terms of price and units sold in Tehran. The objective of this paper is to investigate the facts involved in the housing sector as the safest-growing sector by over 42% inflation. To identify the qualitative and quantitative parameters in the housing market. Therefore, data were analyzed by G.I.S and SPSS software. The Exponential Growth model and Aggregated Indices Randomization Method (AIRM) to forecast the future unit demand. Two important changes in the 2018 report are the main points in this research. First, the total number of units sold by the real estate agents was 14900 which dramatically dropped in comparison to a month before by, 22.1% and in comparison to last year at the same time at 3.1%. Second, the price of each apartment unit in comparison to the last month was 8.9%, and in comparison to the same time in last year, 45.8% increased. Results: However, these changes among 22 regions of Tehran are not the same, and regions 1, 2, 4, 5, 7,8,10, 11, 14, and 15 have the biggest share in the housing sold in the market by a total of 71.6% of sold units in May 2018. In particular, Region 5 is one of the most attractive (invest and living) and fast-growing regions in Tehran. The analysis shows that region 5 in the north part of Tehran is developing faster than other regions due to geographical location and its situation in Tehran spatial organization. This research showed that under economic crisis and very high inflation housing is the safest and fast-growing sector. Moreover, Tehran’s spatial organization and ecological foundations introduce the land suitability and different quality of living, and the housing market in Tehran growing uneven and these two introduce and guide the housing market in Tehran.